Analisis Minat Karir Pada Bidang Perpajakan Atas Dasar Motivasi, Persepsi Dan Pengetahuan Pajak - Reginalin Syukur, Faustina; Sitinjak, Norman Duma (University of Merdeka Malang, 2025)
A career in the taxation sector continues to be a potential field of work. Many business sectors are related to taxes. There is always a need for many tax workers, but a tax career is not yet a dream, including for accounting students. Tax careers include being a civil servant in Tax, tax consultant, tax staff (private companies). This research examines career interest in the field of taxation using motivation, perception and knowledge of taxation. Respondents are accounting students at Merdeka University, Malang. The analysis technique used is quantitative descriptive using SPSS Statistics 20. Of the three variables used to test interest in a career in taxation, the results show that perceptions are able to influence students to pursue a career in taxation. Motivation and knowledge of taxation cannot influence students to have an interest in a career in the tax fieldÂ